2014
DOI: 10.1186/1479-5876-12-140
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TCM constitutions of adult Chinese women in Hong Kong and identification of related influencing factors: a cross-sectional survey

Abstract: BackgroundTraditional Chinese Medicine Constitution (TCMC) refers to an integrated, metastable and natural specialty of individual in morphosis, physiological functions and psychological conditions. It is formed on the basis of innate and acquired endowments in the human life process, which can be divided into normal constitution and unbalanced ones. The aim of this study was to investigate the distribution of TCMCs of Chinese women in Hong Kong and its acquired influencing factors.MethodsLocal Chinese women b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 3 publications
(3 reference statements)
5
30
0
1
Order By: Relevance
“…BC is modifiable and may transform as time passes or when a crucial health event occurs [ 38 ]. An epidemiological study revealed that the factors influencing BC include emotions, body weight, educational level, mental work, age, and exercise habit [ 39 ]. Chinese people have endeavored to improve their health for the past thousand years by adjusting their unbalanced BC status.…”
Section: Discussionmentioning
confidence: 99%
“…BC is modifiable and may transform as time passes or when a crucial health event occurs [ 38 ]. An epidemiological study revealed that the factors influencing BC include emotions, body weight, educational level, mental work, age, and exercise habit [ 39 ]. Chinese people have endeavored to improve their health for the past thousand years by adjusting their unbalanced BC status.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutional consideration not only determines the patient's susceptibility to certain pathogens and diseases but is also closely related to the development, treatment, and prognosis of diseases [ 9 ]. When an individual's constitution is evaluated, the congenital hereditary factor, physiological functions, psychological conditions, and social factor are usually taken into account, suggesting that the constitution has a close relationship with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…每种体质都有其特定的生理 和心理特征, 存在某些(或某类)疾病的发病倾向性, 应 区别对待 [5] . 中医体质学理念为健康促进提供了一个 全新的思维方式 [6] . 2009年, 中华中医药学会颁布了 《中医体质分类与判定》标准, 体质辨识及分类方法 在全国得到推广应用 [7] .…”
Section: 摘要unclassified